Genetic Relationship Between Endometriosis and Melanoma - Yang, Fei; Mortlock, Sally; MacGregor, Stuart; Iles, Mark M.; Landi, Maria Teresa; Shi, Jianxin; Law, Matthew H.; Montgomery, Grant W. (Frontiers in Reproductive Health, 2021)
Epidemiological studies have observed that risk of endometriosis is associated with history of cutaneous melanoma and vice versa. Evidence for shared biological mechanisms between the two traits is limited. The aim of this study was to investigate the genetic correlation and causal relationship between endometriosis and melanoma. Summary statistics from genome-wide association meta-analyses (GWAS) for endometriosis and melanoma were used to estimate the genetic correlation between the traits and Mendelian randomisation was used to test for a causal association. When using summary statistics from separate female and male melanoma cohorts we identified a significant positive genetic correlation between melanoma in females and endometriosis (rg = 0.144, se = 0.065, p-value = 0.025). However, we find no evidence of a correlation between endometriosis and melanoma in males or a combined melanoma dataset. Endometriosis was not genetically correlated with skin colour, red hair, childhood sunburn occasions, ease of skin tanning or nevus count suggesting that the correlation between endometriosis and melanoma in females is unlikely to be influenced by pigmentary traits. There was evidence of a significant causal relationship between the genetic risk of melanoma in females and endometriosis. Colocalization analysis identified 27 genomic loci jointly associated with the two diseases regions that contain different causal variants influencing each trait independently. This study provides evidence of a small genetic correlation and potentially causal relationship between the genetic risk of melanoma in females and endometriosis. Larger GWAS studies with increased power will be required to further investigate these associations.